Sensory Evaluation and Metabolomic Analysis of Lycium Leave Tea - LU Li, ZHOU Chengzhe, XU Kai, ZHANG Mengcong, WEN Shengjing, DUAN Linyuan, TIAN Caiyun, SHI Biying, ZHANG Bo, GUO Yuqiong (Shipin Kexue, 2024)
The sensory quality and metabolite profiles of the fresh and dried buds and leaves of Lycium from 26 cultivars (lines) were analyzed by sensory evaluation and metabolomics combined with multivariate statistical analysis. The results of sensory evaluation showed that the dried buds and leaves of Lycium had a mellow, fresh and sweet taste, and by liquid chromatography-mass spectrometry (LC-MS), 879 metabolites were identified in Lycium buds and leaves, including amino acids and their derivatives, flavonoids, phenolic acids, saccharides, nucleotides and their derivatives, lignans and coumarins, alkaloids, terpenoids, organic acids, and lipids. Using partial least square discriminant analysis (PLS-DA) model and one-way analysis of variance (ANOVA), 211 differential metabolites were selected, which were mainly enriched in the linoleic acid metabolism, flavonoid biosynthesis, flavonoids and flavanols biosynthesis, phenylpropanol biosynthesis, and galactose metabolism pathways. In addition, it was found that amino acids and their derivatives, flavonoids, sugars, and lipids were important components to discriminate the metabolites of different cultivars (lines). Partial least squares regression (PLSR) analysis showed that 26 metabolites including epicatechin, isoquercitrin, and rutin collectively affected the taste of Lycium tea such as mellow, thick, fresh, sweet and bitter. The results of sensory evaluation and PLSR analysis showed that seven cultivars (lines) of Lycium including ‘Ningqicai No. 1’, ‘Ningqi No. 9’, Z90, Z68, Q3, Q6-13, and Z48 had better sensory quality and rich flavor substances.